Supercritical CO2 extraction of spent coffee grounds. Influence of co-solvents and characterization of the extracts - Coelho, Jose (2020)
Spent coffee grounds (SCGs) were extracted with supercritical CO2 at temperatures of 313 K and 333 K, pressures up to 50.0 MPa and different scCO(2) flow rates. The addition of co-solvents isopropanol, ethanol and ethyl lactate decreased the time to achieve the maximum oil yield, to half of that with pure CO2. Analysis of the extracted oils by NMR, showed that caffeine content was (0.56-3.96) % and DUFA and MUFA contents changed within (39.8-42.0) % and (12.9-15.8) %, respectively. The analyses of fatty acids performed by GC-FID revealed the composition of the oils being 76 % of the total constituted by palmitic and linoleic esters. The DPPH antioxidant capacity was improved up to 12.5 times with co-solvents. The kinetics of oil extraction from SCGs with pure scCO(2) was modeled successfully by combining for the first time representation of the oil mixture by a single virtual molecule with group contribution methods.